The Flexible Thinking and its Relationship to the Cognitive Motivation and the Social Interaction among University Students - Duraid Ahmed, Susan; Hussein Qalander, Sahla (Opción, 2019)
The research aims to identify the relationship between flexible thinking, cog- nitive motivation and social interaction among university students. Therefore, a sample of (320) students from the morning study from the College of Ed- ucation for Pure Sciences / Ibn Al-Haytham was used for the academic year (2018-2019). The use of three tools to achieve the requirements of the research: the test of flexible thinking prepared by (Ola Ahmed al-Jallad) (2016), the measure of cognitive motivation prepared by (Shaarawy, 2010). Using the statistical methods of unilateral and binary variance analysis and the Schiff equation, the results indicate that the university students have a good level of flexible thinking, cognitive motivation and social interaction.